Governança no setor público: um estudo de caso no município de São Caetano do Sul - Vieira, Andréa Marissol dos Santos (2010)
The need to keep up the fast evolution in the developmental process make that being proposed several mechanisms that help to the achievement of such needs. Among these mechanisms we highlight the Corporate Governance, a concept that preaches the practice of equity, ethic, transparency and responsability in the conduct of the management in organizations, in order to provide sustainability and longevity to them. When referring to the adoption of practices that preach these concepts, we understand that these recommendations derive from conflicts that occur within organizations, arising from imperfectly symmetrical interests between managers and owners of capital, these conflicts are called Agency Conflicts; And in this context, the using of practices of corporate governance is presented as a way to make pleasant such conflicts Mapping a parallel between private administration and public administration also see the existence of conflicts of similar interests, but in this case, between public managers and citizens and by analogy we can conclude that the use of the mentioned corporate governance practices in public administration, also help to make pleasant such conflicts. Starting this assumption associated with growing concern expressed in several parts of the world to encourage the adoption of corporate governance practices in public management, we build on for the present work, a study published by the Public Sector Committee in together with the International Federation of Accountants (PSC IFAC) called Study 13 in which there is a discussion on the topic Corporate Governance and Public Management. To prepare this, we conducted a case study based on the city of São Caetano do Sul, for present the peculiar characteristics to a Brazilian city and set out to examine the management of the current administration (2008/2009) with the objective of confront the management practices adopted by management publishes sulsancaetanense with the recommendations of corporate governance practices in public administration developed in the study 13 of PSC / IFAC. The results achieved through the present, indicate that public management has been progressively adopting the corporate governance practices recommended in the study 13, but needs to improve the way given to practices of ACCOUNTABILITY AND DISCLOSURE that testify that need to be better enforced, so we conclude the present with recommendations that may contribute to enhance such practices, aiming so, awake the interest of the other researchers for issues related to the theme of our research